How single-cell techniques help us look into lung cancer heterogeneity and immunotherapy - Liao, Pu; Huang, Qi; Zhang, Jiwei; Su, Yuan; Xiao, Rui; Luo, Shengquan; Wu, Zengbao; Zhu, Liping; Li, Jiansha; Hu, Qinghua (Frontiers in Immunology, 2023)
Lung cancer patients tend to have strong intratumoral and intertumoral heterogeneity and complex tumor microenvironment, which are major contributors to the efficacy of and drug resistance to immunotherapy. From a new perspective, single-cell techniques offer an innovative way to look at the intricate cellular interactions between tumors and the immune system and help us gain insights into lung cancer and its response to immunotherapy. This article reviews the application of single-cell techniques in lung cancer, with focuses directed on the heterogeneity of lung cancer and the efficacy of immunotherapy. This review provides both theoretical and experimental information for the future development of immunotherapy and personalized treatment for the management of lung cancer.